The rivers and their fantastic beings from Amazonian literature - Sales, Maria da Luz Lima; de Sousa, Carlos Wilker Silva; Mendes , Luiz Henrique Rocha (Seven Editora, 2024)
The research deals with the elements that unite the popular imagination and the rivers of the Amazon. The river has unrevealed secrets that allow the creation of supernatural narratives and phenomena, providing the formation of a unique literary identity, surrounded by mysteries and fantastic beings. From this arises the objective of understanding the role of the river and its aspects in the construction of Amazonian literariness. Documentary research was used, which was guided by three types of reading: exploratory, analytical and comparative. The research was based mainly on Loureiro’s literary theory, published in Cultura Amazônica: uma poética do imaginário, which uses a plurivalent methodological approach, passing through aesthetics and socioethnoanthropology, to "wander" through the Amazonian culture. As a result, three themes related to the mythological apparatus of the Amazonian aquifer were selected: the Boto, seducer of the Amazonian waters; the fearsome snakes of the Amazon; and the enchantments of the waters. Each category formulated sought to debate the origins, forms and symbolic representations of its contents. Thus, the present work intends to contribute to the expansion of studies on this theme and to form a small theoretical framework that allows us to understand the meaning of local mythopoetics in regional cultural formation. DOI:https://doi.org/10.56238/sevened2024.018-027